Social Mindfulness and Psychosis: Neural Response to Socially Mindful Behavior in First-Episode Psychosis and Patients at Clinical High-Risk - Lemmers-Jansen, Imke L. J.; Fett, Anne-Kathrin J.; Van Doesum, Niels J.; Van Lange, Paul A. M.; Veltman, Dick J.; Krabbendam, Lydia (Frontiers in Human Neuroscience, 2019)
Background: Psychosis is characterized by problems in social functioning and trust, the assumed glue to positive social relations. But what helps building trust? A prime candidate could be social mindfulness, the ability and willingness to see and consider another person’s needs and wishes during social decisions. We investigated whether first-episode psychosis patients (FEP) and patients at clinical high-risk (CHR) show reduced social mindfulness, and examined the underlying neural mechanisms. Methods: Twenty FEP, 17 CHR and 46 healthy controls, aged 16-31 performed the social mindfulness task (SoMi) during fMRI scanning, spontaneously and after instruction “to keep the other’s best interest in mind”. As first of two people, participants had to choose one out of four products, of which three were identical and one was unique, differing in a single aspect (e.g., color). Results: FEP tended to choose the unique item (unmindful choice) more often than controls. After instruction, all groups significantly increased the number of mindful choices compared to the spontaneous condition. FEP showed reduced activation of the caudate and medial prefrontal cortex (mPFC) during mindful, and of the anterior cingulate cortex (ACC), mPFC, and left dorso-lateral prefrontal cortex (dlPFC) during unmindful decisions. CHR showed reduced activation of the ACC compared to controls. Discussion: FEP showed a trend towards more unmindful choices. A similar increase of mindful choices after instruction indicated the ability for social mindfulness when prompted. Results suggested reduced sensitivity to the rewarding aspects of social mindfulness in FEP, and reduced consideration for the other player. FEP (and CHR to a lesser extent) might perceive unmindful choices as less incongruent with the automatic mindful responses than controls. Reduced socially mindful behavior in FEP may hinder the building of trust and cooperative interactions.